To Empower People : The role of mediating structures in public policy - Berger, Peter L.; Neuhaus, Richard John.; American Enterprise Institute for Public Policy Research (Washington : American Enterprise Institute for Public Policy Research, 1977)
in 1975, the authors initiated a research project whose purpose was to explore the role of mediating structures in public policy. This essay introduces the basic idea of the project, suggests some possible policy implications, and indicates the areas and directions of future research effort.
ne 5/06/2018
Loan
Keywords: Social policy; Social institutions